Effect of medicinal plants and natural products on liver enzymes in non-alcoholic fatty liver patients in iran: A systematic review and meta-analysis - Moloud Fakhri; Hafez Fakheri; Mohammad Azadbakht; Mahmood Moosazadeh; Seyde Sedighe Yousefi (International Journal of Preventive Medicine, 2022)
Background: Nonalcoholic fatty liver is the most common chronic liver disease. Regarding the side effects of synthetic medicines and the variety of natural products in Iran climate, the present study aimed to investigate the effect of medicinal plants and natural products on liver enzymes in patients with non-alcoholic fatty liver disease in Iran using meta-analysis. Methods: To extract the intended studies, internal and external databases, including SID, Magiran, IranDoc, PubMed, Scopus, Web of Science, Embase, Cochrane, and Clinical Trial Registration System of Clinical trial.gov, the ISRCTN system, as well as Clinical Trial Registration System affiliated to the World Health Organization were searched. The obtained data were analyzed in STATA.14 software. A P value less than 0.05 was considered statistically significant. Results: A total of 44 rstudies were reviewed with a sample size of 1298 participant; they were published in the period from 2009 to 2018, silymarin had the highest effect on the reduction of AST (SMD = -2.68), cinnamon excreted the most profound effect on ALT (SMD = -2.69). In addition, cinnamon had the highest effect on gamma-glutamyl transferase (GGT) (SMD:-3.17), and curcumin had the highest effect on alkaline phosphatase (ALP) (SMD = -1.88). In the lipid profile, the effect of medicinal herbs and natural products on lowering total cholesterol and LDL was statistically significant. In the glycemic profile, the effect of medicinal plants and natural products on the reduction of fasting blood sugar, insulin, and hemoglobin A1c levels was statistically significant. Conclusions: As evidenced by the obtained results, the highest effect of using natural products was observed in the reduction of GGT, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) levels, respectively; nonetheless, the effect of natural products on ALP reduction was not statistically significant.